Current Basic and Pathological Approaches to the Function of Muscle Cells and Tissues From Molecules to Humans - Sugi, Haruo (IntechOpen, 2012)
This volume contains 17 short review articles classified into 3 parts. Part I consists of 7 articles dealing with basic aspects of contractile mechanism in skeletal and smooth muscle cells and also function of melanocytes having many properties common to those of smooth muscles. Part II and Part III contain articles dealing with pathological aspects of cardiac and smooth muscle cell functions, and dealing with factors influencing structure and function of cardiac and smooth muscle cells and tissues. The Editor believes that these articles are stimulating and informative for readers interested in basic, pathological and clinical aspects of muscle cells and tissues.